Copper binding in IscA inhibits iron-sulfur cluster assembly in Escherichia coli - Tan, Guoqiang (2014)
Among the iron-sulfur cluster assembly proteins encoded by gene cluster iscSUA-hscBA-fdx in Escherichia coli, IscA has a unique and strong iron binding activity and can provide iron for iron-sulfur cluster assembly in proteins in vitro. Deletion of IscA and its paralogue SufA results in an E. coli mutant that fails to assemble [4Fe-4S] clusters in proteins under aerobic conditions, suggesting that IscA has a crucial role for iron-sulfur cluster biogenesis. Here we report that among the iron-sulfur cluster assembly proteins, IscA also has a strong and specific binding activity for Cu(I) in vivo and in vitro. The Cu(I) center in IscA is stable and resistant to oxidation under aerobic conditions. Mutation of the conserved cysteine residues that are essential for the iron binding in IscA abolishes the copper binding activity, indicating that copper and iron may share the same binding site in the protein. Additional studies reveal that copper can compete with iron for the metal binding site in IscA and effectively inhibits the IscA-mediated [4Fe-4S] cluster assembly in E. coli cells. The results suggest that copper may not only attack the [4Fe-4S] clusters in dehydratases, but also block the [4Fe-4S] cluster assembly in proteins by targeting IscA in cells.